2020
DOI: 10.1080/09515070.2020.1777390
|View full text |Cite
|
Sign up to set email alerts
|

Psychotherapy at a public hospital in the time of COVID-19: telehealth and implications for practice

Abstract: As the crisis of global pandemic continues to unfold and alter the everyday workings of public life, early trends in the impact on mental healthcare treatment at a safety-net hospital illuminate implications for clinical work in the public sector under unprecedented conditions and beyond. While there are many important areas to consider and research to come, the current paper will explore the impact of the COVID-19 crisis on attendance of psychotherapy sessions. The authors point to early evidence from their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 12 publications
(9 reference statements)
2
20
0
Order By: Relevance
“…Therefore, it allowed practitioners to reach more patients. Similar results were published by Silver Z. et al They noticed a decrease in the rate of missed appointments after a transition to remote sessions with patients in public hospitals throughout the time of COVID-19 [9]. Chen C. et al illustrated with clinical material some benefits of telepsychological sessions to therapeutic relationships, i.e., more safety, intimacy, and closeness, new topics, created by the absence of the other [10].…”
Section: Introductionsupporting
confidence: 73%
“…Therefore, it allowed practitioners to reach more patients. Similar results were published by Silver Z. et al They noticed a decrease in the rate of missed appointments after a transition to remote sessions with patients in public hospitals throughout the time of COVID-19 [9]. Chen C. et al illustrated with clinical material some benefits of telepsychological sessions to therapeutic relationships, i.e., more safety, intimacy, and closeness, new topics, created by the absence of the other [10].…”
Section: Introductionsupporting
confidence: 73%
“…20 Open access to virtual behavioral health visits can lower the rate of no-shows, demonstrating how accommodating diverse modalities to behavioral health eases access to treatment. 21 Decriminalization And Crisis Response ▸ CRIMINALIZATION OF BEHAVIORAL HEALTH CONDITIONS: Police often play a central role in the lives of people with serious mental illness. Today 7-10 percent of police encounters involve mental illness, and an estimated two million people with serious mental illnesses cycle through the nation's jails every year.…”
Section: Policy Goalsmentioning
confidence: 99%
“…Results from clinical trials and meta -analyses have shown that ERP is comparably effective when delivered in person, via telephone, or through telehealth [7] , [23] . Furthermore, initial reports from the start of the pandemic show that when transitioning to telehealth, either via telephone or video mediated, patients continued to engage in treatment with no significant difference in outcomes [20] . Additionally, home-based exposures have become easier to conduct through telehealth [18] .…”
Section: Telehealthmentioning
confidence: 99%